Extension in community-based coastal resources management of Ban Bay, Aklan, Philippines - Catedrilla, Liah C. (Danyag : Journal of Humanities and Social Sciences, 2000)
This study describes the conduct of extension in the community-based coastal resources management (CBCRM) of Batan Bay in the province of Aklan. It also identifies the problems in the CVCRM extension delivery system and shows the role of extension in the development of effective educational strategies for communities within the CBCRM framework. The respondents of the study include fisherfolk from three coastal barangays; fisheries technicians of the municipalities of Altavas, Bataan, and New Washington; personnel of the University of the Philippines involved in the Local Government Cooperation for Coastal Resources management projects; and seven local government officials.